2016
DOI: 10.5213/inj.1632712.356
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanism of Interstitial Cystitis/Bladder Pain Syndrome and Mapping the Heterogeneity of Disease

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a heterogeneous syndrome which is usually characterized by urinary frequency, nocturia, and bladder pain. Several pathomechanisms have been proposed, including uroepithelial dysfunction, mast cell activation, neurogenic inflammation, autoimmunity, and occult urinary tract infections. It is possible that an inflammatory process alters regulation of urothelial homeostasis and results in dysfunction of the bladder epithelium. Different phenotypes of IC/BPS h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 102 publications
1
73
1
2
Order By: Relevance
“…Interstitial cystitis/bladder pain syndrome (IC/BPS), is a disease condition characterized by bladder pain, frequent urination, urgency, and nocturia . There have been many reports concerning the pathophysiology of IC/BPS including uroepithelial dysfunction, mast cell activation, neurogenic inflammation, but the accurate etiology remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial cystitis/bladder pain syndrome (IC/BPS), is a disease condition characterized by bladder pain, frequent urination, urgency, and nocturia . There have been many reports concerning the pathophysiology of IC/BPS including uroepithelial dysfunction, mast cell activation, neurogenic inflammation, but the accurate etiology remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Причины развития СБМП до конца не-ясны. В качестве возможных причин его развития рассматривают уротелиальные дисфункции, акти-вацию тучных клеток, аутоиммунные, нейрогенные и ишемические нарушения, инфекционное воспа-ление [5][6][7]. В основе диагностики СБМП лежит оценка симптоматики заболевания, результатов цистоскопии и биопсии стенки мочевого пузыря при обязательном исключении других возможных причин появления боли и расстройств мочеиспу-скания [8][9][10].…”
Section: Introductionunclassified
“…24 Heredity might play a role in the pathogenesis of BPS. In 2004 study found that prevalence of BPS in females who have a first-degree relative with confirmed BPS is 1,431 per 100,000.5 In comparison, the prevalence rate in the general population is estimated to be about 60 per 100,000.…”
Section: Risk Factorsmentioning
confidence: 99%